2004
DOI: 10.3989/cyv.2004.v43.i2.565
|View full text |Cite
|
Sign up to set email alerts
|

Desarrollo de filtros interferenciales para emisores fotoluminiscentes basados en silicio poroso

Abstract: Las propiedades fotoluminiscentes y electroluminiscentes en el visible del silicio poroso hacen de éste un material muy interesante para el desarrollo de disposotivos optoelectrónicos. Para la obtención de dispositivos de calidad es necesario reducir la semianchura del espectro de luminiscencia del silicio poroso, típicamente de unos 100 nm, para conseguir una emisión monocromática. Esto puede conseguirse formando sobre la capa luminiscente una estructura multicapa, también de silicio poroso, que actúe a modo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The porosity and the thickness for each monolayer of Psi are measured using gravimetric methods. To get the refractive index of each Psi monolayer, we used the effective medium theory of Bruggeman, while considering that we have a homogeneous medium that is associated with an effective dielectric function [ 20 ]. This effective dielectric function is related to the dielectric functions of the two mediums forming this material (air and silicon), where it is assumed that all of the pores or islands of the bulk material experience an average electric field [ 21 ]; the equation is expressed as follows: where is the volume fraction of air within the Psi layer (porosity); is the dielectric function of air; is the dielectric function of c-Si, and represents the dielectric function of Psi; and, is the volume fraction of c-Si in the porous layer.…”
Section: Methodsmentioning
confidence: 99%
“…The porosity and the thickness for each monolayer of Psi are measured using gravimetric methods. To get the refractive index of each Psi monolayer, we used the effective medium theory of Bruggeman, while considering that we have a homogeneous medium that is associated with an effective dielectric function [ 20 ]. This effective dielectric function is related to the dielectric functions of the two mediums forming this material (air and silicon), where it is assumed that all of the pores or islands of the bulk material experience an average electric field [ 21 ]; the equation is expressed as follows: where is the volume fraction of air within the Psi layer (porosity); is the dielectric function of air; is the dielectric function of c-Si, and represents the dielectric function of Psi; and, is the volume fraction of c-Si in the porous layer.…”
Section: Methodsmentioning
confidence: 99%
“…The porosity and the thickness for each monolayer of Psi are measured using gravimetric methods. To get the refractive index of each Psi monolayer, we used the effective medium theory of Bruggeman, while considering that we have a homogeneous medium that is associated with an effective dielectric function [20]. This effective dielectric function is related to the dielectric functions of the two mediums forming this material (air and silicon), where it is assumed that all of the pores or islands of the bulk material experience an average electric field [21]; the equation is expressed as follows:…”
Section: Porous Silicon Refractive Indexmentioning
confidence: 99%
“…It can thus be assumed that the oxidized PS structure is composed by three components: crystalline silicon, silicon oxide and air [31]. The refractive index (n pso ) of the oxidized PS-ML was calculated using a model that considers the three media [15]. The equation that supports that model is as follows (Eq.…”
Section: -2mentioning
confidence: 99%
“…Both oxidation steps were conducted at atmospheric pressure. The RI of air, silicon and silicon oxide were calculated to predict the maxima of the re-flectance peak in the UV region [15]. It is suggested that the fabricated UV-DBR would be a suitable candidates for applications in short-wavelength devices since the formed structures are nano-sized PS with wide band-gap [16,17].…”
Section: Introductionmentioning
confidence: 99%